2017
DOI: 10.1161/atvbaha.116.308615
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of Calcific Aortic Valve Disease

Abstract: Calcific Aortic Valve Disease (CAVD) is a highly prevalent cardiovascular disorder accounting for a rising economic and social burden on aging populations. In spite of continuing study on the pathophysiology of disease, there remain no medical therapies to prevent the progression of CAVD. The discovery of biomarkers represents a potentially complementary approach in stratifying risk and timing of intervention in CAVD, and has the advantage of providing insight into causal factors for the disease. Biomarkers ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
67
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(72 citation statements)
references
References 76 publications
(81 reference statements)
4
67
0
1
Order By: Relevance
“…9 Investigations of various bacteria have identified different mechanisms that promote calcification of tissues. 5,7 Molecular biological studies of the heart valve tissue of patients with sVHD have confirmed the detection of bacteria. 8,10 The literature reveals positive evidence for streptococci, 8 staphylococci, and Propionibacterium, 10 Chlamydophila, and Mycoplasma 11 on the basis of polymerase chain reaction studies.…”
Section: Perspectivementioning
confidence: 96%
See 1 more Smart Citation
“…9 Investigations of various bacteria have identified different mechanisms that promote calcification of tissues. 5,7 Molecular biological studies of the heart valve tissue of patients with sVHD have confirmed the detection of bacteria. 8,10 The literature reveals positive evidence for streptococci, 8 staphylococci, and Propionibacterium, 10 Chlamydophila, and Mycoplasma 11 on the basis of polymerase chain reaction studies.…”
Section: Perspectivementioning
confidence: 96%
“…[2][3][4] For years, it has been suggested that classical cardiovascular risk factors such as diabetes, hyperlipidemia, arterial hypertension, smoking, and familial predisposition promote the pathogenesis of calcific aortic valve stenosis. 5,6 In addition to a disturbed calcium metabolism and immunological influences, 7 in particular subacute or acute endocarditis is responsible for the development of sVHD. 8 In 2004 Cohen and colleagues 9 confirmed a link between subclinical bacterial endocarditis and calcification of the aortic valve in an animal model.…”
Section: Perspectivementioning
confidence: 99%
“…Recently, a large amount of data is also gathered on the role of biomarkers in aortic stenosis. [35][36][37] NT-proBNP levels correlate with AS severity and echocardiographic markers of higher risk for adverse outcomes in AS. [38] ST2 has shown to correlate with AS severity, symptoms and prognosis.…”
Section: Plos Onementioning
confidence: 99%
“…Nevertheless, whether an association of AVC with carotid artery lesions and PAD exists in predialysis patients remains unknown. Furthermore, especially in patients with CKD, in addition to traditional CV risk factors, nontraditional CV risk factors such as renal dysfunction itself and deranged mineral metabolism [e.g., hyperphosphatemia, elevated parathyroid hormone (PTH) or fibroblast growth factor 23 (FGF23)] associated with CKD are also associated with AVC [28][29][30][31][32]. However, in predialysis patients, the association of AVC with carotid artery lesions and PAD beyond both traditional and nontraditional CV risk factors remains uncertain.…”
Section: Introductionmentioning
confidence: 99%